2013
DOI: 10.1016/j.thromres.2012.12.003
|View full text |Cite
|
Sign up to set email alerts
|

Factor XIII improves platelet adhesion to fibrinogen by protein disulfide isomerase-mediated activity

Abstract: Background: Factor XIII (FXIII), a plasma pro-transglutaminase, consists of two A subunits and two B subunits (FXIIIA2B2). Following activation by thrombin, it cross-links fibrin chains at the final step of coagulation. We previously reported that FXIII subunit A (FXIIIA) serves as a protein disulfide isomerase (PDI), and that PDI promotes platelet adhesion and aggregation. Objective: This study sought to examine possible mechanistic effect of FXIII on platelet adhesion to fibrinogen; specifically, the role of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 23 publications
0
3
0
1
Order By: Relevance
“…Although multiple mechanisms alter platelet function in the context of liver regeneration [39], FXIII-induced cross-linking stabilizes fibrin [40], and this may be critical to drive platelet accumulation in the early moments after PHx. Moreover, multiple studies have shown that FXIII directly contributes to platelet adhesion to fibrin and drives platelet responses secondary to fibrin(ogen)-integrin α IIb β 3 engagement [41][42][43]. In addition to platelets, fibrin engagement of leukocyte β2 integrins [44] could contribute to liver regeneration by modulating effector functions of either neutrophils or macrophages, both cell types linked to liver regeneration in mice and humans [45,46].…”
Section: Impact Of Fxiii Deficiency On Hepatocyte Proliferation After...mentioning
confidence: 99%
“…Although multiple mechanisms alter platelet function in the context of liver regeneration [39], FXIII-induced cross-linking stabilizes fibrin [40], and this may be critical to drive platelet accumulation in the early moments after PHx. Moreover, multiple studies have shown that FXIII directly contributes to platelet adhesion to fibrin and drives platelet responses secondary to fibrin(ogen)-integrin α IIb β 3 engagement [41][42][43]. In addition to platelets, fibrin engagement of leukocyte β2 integrins [44] could contribute to liver regeneration by modulating effector functions of either neutrophils or macrophages, both cell types linked to liver regeneration in mice and humans [45,46].…”
Section: Impact Of Fxiii Deficiency On Hepatocyte Proliferation After...mentioning
confidence: 99%
“…Cell surface receptors can be activated via binding, but also through cleavage by proteases; kallekrein-14 and cathepsin G are PDI substrates and are known to cleave and activate members of the PAR receptor family (8, 39, 40). PDI can modulate phosphatidylserine (PS) exposure (16, 41) and may regulate coagulation through disulfide regulation of tissue factor, activation of factor XI, maturation of platelet factor V, and attenuating factor XIII cross-linking activity toward fibrin (8, 9, 13, 42, 43). More globally, PDI is believed to sense and regulate the redox state of the extracellular membrane, by interacting with small molecule effectors like glutathione and nitric oxide (NO), and modulating the redox state of other extracellular thiol isomerases (5, 6, 44).…”
Section: Pdi and Thrombus Formationmentioning
confidence: 99%
“…Interaction with either of these receptors leads to platelet activation which can enhance the metastatic potential of the tumor through shielding from an anti-tumor immune response (59, 60, 62). Several cell surface receptors, receptor agonist proteases, and large scaffolding proteins which bind to these receptors across multiple cells and strengthen the thrombus have all been identified as PDI substrates (9, 12, 14, 33, 35, 38, 43).…”
Section: Hypercoagulability Of Cancer and Potential Interface With Pdimentioning
confidence: 99%
“…Это может быть одной из причин тромбозов при АФС. Также показано, что фактор XIII (FXIII; его А-цепь) обладает активностью ПДИ, и тем самым способствует адгезии и агрегации тромбоцитов [43,44].…”
Section: Thiol Isomerases As a Target For Antithrombotic Therapy тиолunclassified